(untitled) (Al-Aasar, 2025)
Cerebral palsy (CP) is a leading cause of motor dysfunction in children, and the hypotonic subtype often leads to significant challenges in motor function and balance. This study evaluates the effects of vestibular stimulation in conjunction with conventional physical therapy on improving balance in children with hypotonic CP. A randomized controlled trial was conducted with 82 children aged 5 to 10 years, assigned to either a vestibular stimulation group or a conventional therapy group. Outcomes were measured using the Pediatric Balance Scale (PBS) and the Gross Motor Function Measure (GMFM). Results indicated significant improvements in balance and motor function in the vestibular stimulation group compared to the conventional group. This suggests that vestibular stimulation can be an effective adjunct to conventional physiotherapy for improving balance and motor function in children with hypotonic cerebral palsy.